2014
DOI: 10.1097/dcr.000000000000000
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on Genetic Evaluation and Management of Lynch Syndrome

Abstract: The Multi-Society Task Force, in collaboration with invited experts, developed guidelines to assist health care providers with the appropriate provision of genetic testing and management of patients at risk for and affected with Lynch syndrome as follows: provides a colorectal cancer risk assessment tool to screen individuals in the office or endoscopy setting; illustrates a strategy for universal screening for Lynch syndrome by tumor testing of patients diagnosed with colorectal cancer; -6 provide algorithms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(22 citation statements)
references
References 96 publications
(143 reference statements)
0
22
0
Order By: Relevance
“…PMS2 mutations are associated with LS, a condition that increases the risk for developing CRC, uterine, ovarian, hepatobiliary, urinary tract, brain, skin, and other gastrointestinal malignancies ( 49 , 92 – 95 ). The exact cancer risks conferred by PMS2 mutations are unclear, but they are thought to be lower than other MMR gene mutations ( 96 ).…”
Section: Resultsmentioning
confidence: 99%
“…PMS2 mutations are associated with LS, a condition that increases the risk for developing CRC, uterine, ovarian, hepatobiliary, urinary tract, brain, skin, and other gastrointestinal malignancies ( 49 , 92 – 95 ). The exact cancer risks conferred by PMS2 mutations are unclear, but they are thought to be lower than other MMR gene mutations ( 96 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they have been considered to be insufficient as independent screening tools. To increase the accuracy of screening for Lynch syndrome, microsatellite instability (MSI) and immunohistochemistry (IHC) are used in cases with colorectal cancer, and when losses of MLH1 and PMS2 proteins are detected using IHC, universal screening, including BRAF testing and analysis for MLH1 promoter methylation, is recommended [ 5 , 6 ]. Similarly, in endometrial cancer, MSI and IHC are useful in screening for Lynch syndrome [ 7 10 ], and the mutation site can be estimated using IHC.…”
Section: Introductionmentioning
confidence: 99%
“…The Revised Bethesda Guidelines recommend MSI analysis and/or IHC analysis of tumor tissue to select patients for definitive DNA sequence analysis [ 12 ]. Our study identified three putative LS patients from Mexico, initially suspected based upon family history and screened by IHC and confirmed with DNA analyses.…”
Section: Discussionmentioning
confidence: 99%